Peridural segmental analgesia in childbirth - Analgesia peridurale segmentaria nel travaglio di parto - Nicola Maratea (Publiediting, 2020)
Childbirth pain is a perfect example of acute pain as somatic, visceral and related components are present. This kind of pain opens up a wide field of study and wide therapeutic possibilities to the algologist. Epidural analgesia in childbirth still presents some limitations, related both to the possible motor block produced by local anesthetics (LAs); they are able to interfere variously on the course of childbirth, as well as potential maternal-fetal toxic effects induced by the possible passage in circulation of the drugs used. Clinically, the best applicable technique is the segmental peridural and the CSE (combined spinal-epidural anesthesia); the technological improvement essentially translates into a reduction of the side effects. With LAs, opioids and intrathecal alpha-2-agonists can be associated as adjuvants.